Succulents for beginners : a year-round growing guide for healthy and beautiful plants - Matsuyama, Misa (Tuttle Publishing, 2022)
"Succulents for Beginners is the perfect introduction to this friendly and forgiving plant family. Misa Matsuyama--the bestselling author of The Gardener's Guide to Succulents--shows you how to plant and maintain the most popular varieties of succulents and cacti with reassuring advice and minimum fuss...The month-by-month format and simple, yet thorough, instructions will have you referring to this handy resource again and again. Gorgeous photos and helpful tips invite you to bring more and more of these plants into your life."--Amazon